Effect of relative humidity on the enhancement of the triboelectrification efficiency utilizing water bridges between triboelectric materials. (March 2022) - Wang, Kun; Qiu, Zhirong; Wang, Jiaxin; Liu, Ye; Chen, Rong; An, Haoqun; Park, Jae Hyeon; Suk, Chan Hee; Wu, Chaoxing; Lin, Jintang; Kim, Tae Whan
Abstract: The emerging triboelectric nanogenerator (TENG) technology has reignited research interests in the well-known triboelectrification. Understanding triboelectrification in different humidity conditions has become essential because the relative humidity is a key factor that influences triboelectricity and the output of TENGs. This study uses a capsule TENG as the experimental platform to investigate the effect of different relative humidity (RH) conditions on the triboelectrification of material pairs commonly used in TENGs. Different from the traditional cognition that the number of triboelectric charges decreases with increasing relative humidity, we find that the commonly used triboelectric material pair has its own unique, optimal, relative humidity. The electric output increases with increasing RH and then decreases as the RH reaches and passes an optimal value. The working mechanism related to the formation of water bridges that leading to the enhanced triboelectrification is discussed. Moreover, we find that the exact optimal RH are existed for commonly used triboelectric material pairs. A data table showing the optimal RH for those commonly used material pairs is provided. We find that most of the optimal RH values are concentrated in a small RH range (28–35%), even though a few material pairs have larger optimal RH values (53%). This study presents new insight into the effect of relative humidity on the performance of TENGs and provides a relatively complete set of data on the optimal RH for commonly used material pairs, which may become a critical reference for those designing working conditions for TENGs. Graphical Abstract: ga1 Highlights: Relative humidity (RH) has a positive effect on enhancing triboelectrification. A capsule TENG is fabricated to study the influence of RH on output performance. Effect of RH on the performance of different material pairs is studied. A data table showing optimal HR for commonly used material pairs is provided.